LABOR PRODUCTIVITY IN ROMANIA'S AGRICULTURE IN THE PERIOD 2011-2020 AND ITS FORECAST FOR 2021-2025 HORIZON - Agatha POPESCU; Cristiana TINDECHE; Alina MĂRCUȚĂ; Liviu MĂRCUȚĂ; Adelaida HONȚUȘ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper analyzed labor productivity in Romania's agriculture in the period 2011-2020 and established the forecast for 2021-2025 horizon using the Eurostat data. The processing procedures included fixed basis index, average growth rate, average annual growth, regression models, determination coefficient, descriptive statistics (mean standard deviation and variation coefficient), comparison methods and forecast modeling. The results proved that agriculture productivity is increasing with a lower growth rate, being deeply influenced on output value, gross value added and labour input. Per 1,000 AWU, agricultural output value decreased by 6.77%, gross value added increased by 12.47% and factor income raised by 20.65%. However, for its level of output value and GVA, Romania comes on the last position and for factor income level it comes on the 15th position in the EU. For agriculture development, labour productivity must be increased paying attention to the key determinants: farm structure and size, labour input, technical endowment, and investment.